Agro-industries for development - Da Silva, Carlos A. (Cabi Ser., 2009)
The development of competitive agro-industries is crucial for creating employment and income opportunities as well as enhancing the quality of and demand for farm products. This book addresses strategies required for improving agro-industrial competitiveness in ways that can generate employment and fight poverty in the developing world.